FACTORS INFLUENCING AGRICULTURAL VOCATIONAL HIGH SCHOOL STUDENTS' INTEREST IN WORKING IN THE AGRICULTURAL SECTOR - Isyanto, Agus Yuniawan; Fatimah, Ai Tusi; Amalia, Lidya Nur (Agric, 2024)
The agricultural sector is one of the sectors that makes a large contribution to labor absorption in Indonesia, however data shows a decline in the rate of labor absorption in the agricultural sector, especially among the younger generation. One effort to increase the number of young workers absorbed in the agricultural sector is through agricultural vocational school education which is expected to grow the interest of agricultural vocational school students to work in the agricultural sector in order to overcome the decline in farmer regeneration in Indonesia. The research objectives are to: (1) Identify the interest of agricultural vocational school students in agriculture to work in the agricultural sector, and (2) analyze the factors that influence agricultural vocational school students' interest in working in the agricultural sector. The research was carried out in September 2023 at one of the vocational schools specializing in agricultural skills in Ciamis Regency. The research sample consisted of 78 students who were determined using cluster random sampling. Agricultural vocational school students' interest in working in the agricultural sector was analyzed descriptively, while the factors that influenced agricultural vocational school students' interest in working in the agricultural sector were analyzed using multiple linear regression analysis. The research results show: (1) The majority of agricultural vocational school students who are interested in working in the agricultural sector are in the medium category, and (2) The social environment, community environment and social status have a significant influence on agricultural vocational school students' interest in working in the agricultural sector, while their parents' income has no significant influence.